1972
DOI: 10.1677/joe.0.0550207
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation Induced by Synthetic Luteinizing Hormone Releasing Factor in Androgen-Sterilized Female Rats

Abstract: It is well known that administration of a single injection of testosterone propionate to newborn female rats results in permanent anovulatory sterility. After puberty these animals show permanent vaginal cornification and their ovaries contain follicles but no corpora lutea (Barraclough, 1961). One of the most important lesions in these rats seems to be a blockade of the pre-ovulatory discharge of luteinizing hormone releasing factor (LH-RF) from the median eminence.Porcine LH-RF has been shown to be a decapep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Puberty was clearly delayed and the gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) surges disappeared by destruction of hypothalamo-pituitary-gonadal axis (Hayashi and Aihara, 1989;1993;Pinilla et al, 1993). The sterility observed in the ESR was reported to be due to the lack of neural circuits regulating the release of GnRH (Borvendeg et at., 1972;Mennin et al, 1974;Hayashi et al, 1991). Together with these results, neonatal treatment of estrogen may cause changes in the organizational pattern of the brain areas responsible for the sexual differentiation and behaviors preceding the normal pubertal process.…”
mentioning
confidence: 99%
“…Puberty was clearly delayed and the gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) surges disappeared by destruction of hypothalamo-pituitary-gonadal axis (Hayashi and Aihara, 1989;1993;Pinilla et al, 1993). The sterility observed in the ESR was reported to be due to the lack of neural circuits regulating the release of GnRH (Borvendeg et at., 1972;Mennin et al, 1974;Hayashi et al, 1991). Together with these results, neonatal treatment of estrogen may cause changes in the organizational pattern of the brain areas responsible for the sexual differentiation and behaviors preceding the normal pubertal process.…”
mentioning
confidence: 99%
“…The ovulation inducing activities of LHRH analogs have been studied in diestrus rats employing the method of Yamasaki and Nakayama [6] and in androgen sterilized female rats by a procedure developed in our laboratory [7].…”
Section: Biological Assay Resultsmentioning
confidence: 99%
“…The pituitary responsiveness of NA500 animals did not seem to differ from that of the controls, for the slightly higher amount of LH-RH required for full ovulation in NA500 animals, as compared with control values, was probably necessary for the release of an amount of LH adequate to overcome the ovarian insensitivity which follows androgenization. Ovaries from NA500 rats in fact require approximately 5-10 times as much exoge nous LH as ovaries from normal females, before they show an equivalent ovulatory response [Segal and Johnson, 1959;Astrada et al, 1969; U ilenbrook and Van der Werff ten Bosch, 1972; Mennin et al, 1974], Previously, it was demonstrated that the pituitaries of androgenized female rats are capable of releasing an ovulatory quota of LH in response to sheep hypothalamic extract [Johnson, 1963] and to synthetic LH-RH [Borvendég et al, 1972]. The present work shows that the pituitary glands of normal and androgenized rats are equivalent in their sensitivity to LH-RH, as reported by Mennin et al [1974], Furthermore, the comparable responsiveness to LH-RH is an indication that androgenized females' pituitaries respond as if they were under hormonal conditions comparable to those of a preovulatory proestrous female.…”
Section: Discussionmentioning
confidence: 99%